Effectiveness and safety of Chinese herbal acupoint application in adult patients with fever and mild-to-moderate COVID-19: a multicenter, randomized, double-blind, placebo-controlled trial - Liu, Yicheng; Shi, Jiaheng; Liu, Xinting; Jiang, Zongchen; Zou, Benliang; Zhang, Rui; Li, Qiuyan; Wang, Peili; Zhang, Chenhao; Wang, Jia; Zhang, Zhixi; Huang, Jiao; et al. (Frontiers in Neurology, 2025)
BackgroundChinese herbal acupoint application (HAA) is recommended by certain guidelines for treating mild-to-moderate COVID-19; however, evidence supporting its effectiveness remains limited. This study aimed to evaluate the effectiveness and safety of HAA in adult patients with fever and mild-to-moderate COVID-19.MethodsThis multicenter, randomized, double-blind, placebo-controlled trial was conducted at six hospitals in China. Overall, 364 participants were randomly assigned in a 1:1 ratio to receive either the herbal or placebo acupoint application. All participants received applications at the Dazhui (GV14) and Feishu (BL13) acupoints three times daily for 2 h per application over 5 days and Fuzheng Jiebiao Decoction orally three times daily, three bags per dose. The primary outcome was complete fever relief time. Secondary outcomes included the onset time of fever reduction, changes in symptom scores, routine blood tests, and acetaminophen usage rates and dosages.ResultsRegarding the primary outcome, HAA significantly reduced complete fever relief time compared to placebo (31.75 vs. 52.00 h; p < 0.0001). Regarding secondary outcomes, the herbal group also demonstrated a shorter onset time of fever reduction than the placebo group (24.35 vs. 34.42 h; p < 0.0001). HAA significantly reduced total symptom scores, particularly fever, headache, and cough symptoms. Moreover, 52 patients (29.05%) in the herbal group used acetaminophen, with a median dosage of 0.3 g (0.3, 0.6), which was significantly lower than that in the placebo group, with 94 patients using 0.6 g (0.3, 0.9; p < 0.05). No significant differences were observed in routine blood test results between the groups (p > 0.05), and no serious adverse events (SAEs) were reported in either group.ConclusionChinese herbal acupoint application effectively and safely shortened the complete fever relief time and onset time of fever reduction; alleviated clinical symptoms, particularly fever, headache, and cough; and reduced the need for antipyretic analgesics in adult patients with fever and mild-to-moderate COVID-19.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=188270, identifier: ChiCTR2200067178.